ANALISIS KUANTITATIF BAKTERI COLIFORM DALAM AIR MINUM PADA DEPOT AIR MINUM ISI ULANG DI ELURAHAN TAHOA KABUPATEN KOLAKA - Sartika Gunawan Putri; Yanti Yanti; Erfina Erfina; Nur Khafifa (Biopedagogia, 2023)
Water is one of the most basic needs of all living things, including humans. Water is essential for life because it serves as a barometer for the quality of human life, specifically health. Drinking water is safe for human consumption if it meets the physical, microbiological, chemical, and radioactive requirements specified in the mandatory and additional parameters. In microbiology, the mandatory parameter for drinking water quality is a total of 0 coliform bacteria per 100 ml. The purpose of this study is to quantify the content of coliform bacteria in drinking water at refill drinking water depots in Tahoa Village, Kolaka Regency, that meet or do not meet the requirements outlined in Permenkes No. 492 of 2010. Six refill drinking water depots in Tahoa Village, Kolaka Regency, were used as samples. The method used in this descriptive quantitative research is the most probable number (MPN), which consists of a prediction test and a confirmation test. The results revealed that coliform bacteria were present in drinking water samples A, B, C, D, E, and F, with MPN index values of 240/100 ml, 240/100 ml, and 96/100 ml, respectively. Based on the results of 38/100 ml and 240/100 ml, it can be concluded that the drinking water at the refill drinking water depot in Tahoa Village, Kolaka Regency, does not meet the requirements of Permenkes No. 492 of 2010.